Association of the Chinese visceral adiposity index with marrow adiposity in postmenopausal females - Zuo, Xiaoyong; Miao, Zeyang; Xu, Run; Shi, Dan; Chang, Shixin; Li, Guanwu; Luo, Peng (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the relationship between the Chinese visceral adiposity index (CVAI) and vertebral proton density fat fraction (PDFF).MethodsThe study included 181 postmenopausal females including 53 normal bone mineral density (BMD), 88 osteopenia, and 40 osteoporosis. Vertebral marrow PDFF was measured using Fat Analysis & Calculation Technique imaging, and BMD was assessed via dual-energy X-ray absorptiometry. Bone turnover biomarkers and lipid metabolism were evaluated. The relationship between CVAI and PDFF was assessed using multivariable linear regression models, generalized additive models, and threshold effect analysis.ResultsThe mean BMD at the lumbar spine increased, and PDFF significantly decreased as quartiles of CVAI increased (P for trends <0.05). Multivariable linear regression analysis revealed a clear negative correlation between CVAI and PDFF (regression coefficient β = −0.251, 95% CI, −0.303 to −0.200; P < 0.001) after adjusting for age, time since menopause, waist circumference, body mass index, physical activity, and lipid profiles. The association with marrow PDFF remained significant (β = −0.202, 95% CI, −0.255 to −0.149, P < 0.001) even after additional adjustment for BMD. Further analysis revealed an L-shaped non-linear relationship between CVAI and marrow PDFF after adjusting for age, time since menopause, waist circumference, body mass index, physical activity, lipid profiles, and BMD. An inflection point was identified at a CVAI of 128.3, below which each one-unit increase in CVAI corresponded to a more substantial decrease in marrow PDFF (β = −0.0055, 95% CI: −0.0064 to −0.0045; P < 0.001). However, above this inflection point, each unit increase in CVAI was not significantly associated with a decrease in marrow PDFF.ConclusionsCVAI exhibited a nonlinear negative association with marrow adiposity within a suitable range, once CVAI crossed a definite threshold, PDFF ceased to increase. This finding suggests that a moderate visceral fat accumulation may enhance skeletal integrity, while excessive visceral fat could potentially have detrimental effects.